2021
DOI: 10.1186/s13662-021-03486-7
|View full text |Cite
|
Sign up to set email alerts
|

Closed-form pricing formula for foreign equity option with credit risk

Abstract: Since credit risk in the over-the-counter (OTC) market has undoubtedly become very important issue, credit risk has to be considered when the options in the OTC market are priced. In this paper, we consider the valuation of foreign equity options with credit risk. In order to derive a closed-form pricing formula of this option, we adopt the partial differential equation (PDE) approach and use the Mellin transform method to solve the PDE. Specifically, triple Mellin transforms are used, and the pricing formula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Yoon and Kim [16] were the first to apply Mellin transforms to calculate vulnerable European option prices. Several recent studies have demonstrated that the Mellin transforms can be used to solve the PDE for many types of financial derivatives with credit risk (path-dependent option [17], exchange option [18], and foreign equity option [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Yoon and Kim [16] were the first to apply Mellin transforms to calculate vulnerable European option prices. Several recent studies have demonstrated that the Mellin transforms can be used to solve the PDE for many types of financial derivatives with credit risk (path-dependent option [17], exchange option [18], and foreign equity option [19]).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wang [11], He et al [12], Kim et al [13] and Jeon et al [14] investigated the pricing of vulnerable options in the presence of stochastic volatility affecting asset price processes. In addition, there have been numerous research on vulnerable options with multi-assets [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%